Detection of Organic Colorants in Historical Painting Layers Using UV Laser Ablation Surface‐Enhanced Raman Microspectroscopy1. (29th October 2014) - Cesaratto, Anna; Leona, Marco; Lombardi, John R.; Comelli, Daniela; Nevin, Austin; Londero, Pablo
Abstract Surface‐enhanced Raman spectroscopy (SERS) has been increasingly used in the study of works of art to identify organic pigments and dyes in paintings, which (depending on the material) are difficult or not possible to detect by other current methods. The application of SERS to the study of paintings has been limited, however, by the lack of a sampling approach with sufficient sensitivity and spatial resolution. We show that ultraviolet laser ablation (LA) sampling coupled with SERS detection can be successfully used to study paint layers. LA‐SERS permitted the isolation of signals from colorants in individual thin paint layers in sample cross‐sections, avoiding contamination from adjacent layers. These results expand the range of analytical applications of SERS demonstrating how the technique can be used to sensitively detect minor organic components in complex matrices. While this is fundamental for the study of cultural heritage, it is also relevant in other fields such as forensic analysis, food science, and pharmacology.